1962
DOI: 10.1001/jama.1962.03050020000006b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the I<sup>131</sup> Sodium o-Iodohippurate Renogram

Abstract: our experience:) We have not been able to reliably differentiate cyst from neoplasm on the basis of the renoscan. In cases of fetal lobulation where neo¬ plasm has been suspected on the basis of pyelog¬ raphy, there has been equal Hg2"3 uptake in the lobular area, thus helping to rule out neoplasm. Through the judicious use of the renal seintiscan in conjunction with excretory urography, the need for more hazardous special studies such as retrograde pyelograms and aortograms can often be avoided.In brief, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

1962
1962
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 1 publication
1
3
0
2
Order By: Relevance
“…Soon thereafter the secretion process and the accumulation of radioactivity in the upper urinary tract begins to be evident. The existence of such a rapid process like "hippuran trapping" supports also Wax's (16) observation, that 15 sec after radiohippuran application to animals it is not possible to find 29°/o of the administered radioactivity in both vascular capacity and background tissue. Moreover, our theoretical study of radiohippuran kinetics in the body (8) might show at the beginning of the curve the presence of a more rapid process than that of secretion.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Soon thereafter the secretion process and the accumulation of radioactivity in the upper urinary tract begins to be evident. The existence of such a rapid process like "hippuran trapping" supports also Wax's (16) observation, that 15 sec after radiohippuran application to animals it is not possible to find 29°/o of the administered radioactivity in both vascular capacity and background tissue. Moreover, our theoretical study of radiohippuran kinetics in the body (8) might show at the beginning of the curve the presence of a more rapid process than that of secretion.…”
Section: Discussionsupporting
confidence: 62%
“…The initial spike of the radioactive tracer renogram represents, according to Winter (18), Zum Winkel et al (19), Meade et al (10) and Lawrence et al (9), the vascular capacity of the kidney plus that of background tissue in the kidney region. Wax et al (16) in experiments with animals demonstrated an overlapping of the phases of the radiohippuran renogram. For clinical purposes it is necessary to know, in which part each process influences the shape of the renogram, to determine better the kidney function.…”
mentioning
confidence: 91%
“…the half-life. Indeed, this has been stressed by several authors (13,17,19,21). Stewart and Haynie (1 8) have taken particular interest in this aspect.…”
Section: Discussionmentioning
confidence: 93%
“…As already mentioned, the first phase was originally thought to represent the Idood flow, while the secondary rise was believed to represent tubular function and the descending part of the curve the excretion in the pelvis and the urine flow. However, thorough investigations, chiefly by Wax and McDonald (21) showed that this division cannot be maintained. T h e first, so-called "vascular" phase, is due predominantly to the functional capacity of the kidney, in the form of glomerular filtration and tubular secretion, and only to a minor extent to its vascular capacity.…”
Section: Discussionmentioning
confidence: 99%
“…B. einer Harnstauung, die renale Leistung wiedergibt. Dabei wird abweichend von Literaturangaben (17,28,53,54) unterstellt, daß Hippuran vor der 120. Sek.…”
Section: Introductionunclassified